Nancy w Krainie Wieprzy. Kilka uwag o "Co?" Romana Polańskiego i recepcji filmu we Włoszech - Skórska, Katarzyna (Załącznik Kulturoznawczy, 2023)
Nancy in the Land of Swines: A Few Reflections on Polanski’s What? and the Film’s Reception in Italy The article discusses Roman Polanski’s lesser-known film What?, made in 1972 in Italy, in Carlo Ponti’s villa. Despite not very favorable general reception immediately after the premiere and later in time, the film was appreciated by Italian critics who admired its intertextual values, self-citations and references to Italian cinema, such as ironic allusions to commedia all’italiana, or Federico Fellini’s works and oneiric atmosphere. The main aim of the text is to present some ways of reinterpreting and reevaluating Polanski’s underrated and almost forgotten movie.